Energy markets and the euro area macroeconomy (European Central Bank (ECB), 2010)
This report aims to analyse euro area energy markets and the impact of energy price changes on the macroeconomy from a monetary policy perspective. The core task of the report is to analyse the impact of energy price developments on output and consumer prices. Nevertheless, understanding the link between energy price fluctuations, inflationary pressures and the role of monetary policy in reacting to such pressure requires a deeper look at the structure of the economy. Energy prices have presented a challenge for the Eurosystem, as the volatility of the energy component of consumer prices has been high since the creation of EMU. At the same time, a look back into the past may not necessarily be very informative for gauging the likely impact of energy price changes on overall inflation in the future. For instance, the reaction of HICP inflation to energy price fluctuations seems to have been more muted during the past decade than in earlier periods such as the 1970s.
Keywords: E52; E58; E44; 330; energy; inflation; macroeconomy; monetary policy; Pass-Through